Contemporary Turkey at a Glance - Kamp, Kristina; Kaya, Ayhan; Keyman, E. Fuat; Onursal Besgul, Ozge (Springer Nature, 2014)
Turkish Studies; Turkish Politics, Society and Culture; Turkish Citizenship; Turkish Minorities; Muslim Identity; Turkish Diaspora